The Impact of Adopting Green Accounting as a Path to Achieve the Sustainable Development Dimensions: An Exploratory Study in the General Company for Fertilizers Manufacturing in the Northern Region / Baiji - Salih, Hadeel (PROSPECTIVE RESEARCHES, 2024)
This research came to shed light on the adoption of green accounting and its impact in achieving the dimensions of sustainable development (the economic, social and environmental dimensions), considering that green accounting is the means through which the extent of organizations’ commitment to preserving the environment can be judged by the information it provides about the environmental costs that it provides. incurred by the organization in this area. To achieve the research objectives and test the hypotheses, the descriptive and analytical approach was used, and on the field side, the questionnaire was distributed to the research sample, which is represented by a group of specialized individuals and workers in the fertilizer industry company in the northern region / Baiji. (50) questionnaires were distributed and (40) valid questionnaires were retrieved for analysis. The research reached a set of conclusions, the most important of which is the existence of a significant impact of green accounting that contributes to enhancing the dimensions of sustainable development. This confirms that the work environment becomes supportive and achieves the dimensions of sustainable development if the concept of accounting is adopted. Completely green in its various operations. The most important thing that the researcher recommends is the need for the responsible government agencies to pay attention to solving environmental problems and preserving the environment, including the soil, water resources, plants and animals it contains